Involvement of Oxytocin Receptor/Erk/MAPK Signaling in the mPFC in Early Life Stress-Induced Autistic-Like Behaviors - Wei, Jinbao; Ma, Le; Ju, Peijun; Yang, Beibei; Wang, Yong-Xiang; Chen, Jinghong (Frontiers in Cell and Developmental Biology, 2020)
Neonatal or infant period is a critical stage for the development of brain neuroplasticity. Early life stresses in the neonatal period, including neonatal maternal separation (NMS), have adverse effects on increased risk of psychiatric disorders in juveniles and adults. However, the underlying molecular mechanisms are not largely understood. Here, we found that juvenile rats subjected to daily 4 hour NMS during postnatal day (PND) 1-PND 20 exhibited autism-like behavioral deficits without impairments in learning and memory functions. Molecular mechanism studies showed that oxytocin receptor (OXTR) in the prefrontal cortex (PFC) of NMS rats was evidently down-regulated when compared with control pups. Erk/MAPK signaling, the downstream coupling signaling of OTXR, was also inhibited in NMS juvenile rats. Treatment with oxytocin could relieve NMS-induced social deficit behaviors and activated phosphorylation of Erk/MAPK signaling. Furthermore, Medication with the inhibitor of H3K4 demethylase alleviated the abnormal behaviors in NMS rats, increased the expression of OXTR in PFC, which showed an epigenetic mechanism underlying social deficits induced by NMS. Taken together, these findings identified a molecular mechanism by which disruptions of mother-infant interactions influenced later displays of typical social behaviors and suggested the potential for neonatal maternal separation driven epigenetic tuning of OXTR expression.